Geophysical investigation of subsurface mineral potentials in North-Central Nigeria: implications for sustainable mining and development - Ema M. Abraham; Arinze E. Uwaezuoke; Ayatu O. Usman (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract This study presents the first comprehensive geomagnetic investigation of subsurface mineral potentials in north-central Nigeria, marking a significant advancement in sustainable mining exploration for this resource-rich region. Through an integrated approach using Source Parameter Imaging (SPI), Analytic Signal (AS), Phase Symmetry (PS), Euler Deconvolution (ED), and 3D inversion modeling, we delineate mineralized zones at depths of 150–800 m. The analysis reveals NE-SW, NW-SE, and E-W fault and fracture networks that channel mineral-rich fluids, offering new insights into regional tectonics and mineralization processes. The integration of ED with 3D inversion modeling provides reliable estimates of the location, depth, and geometry of magnetic sources, enhancing the targeting of potential ore bodies and reducing exploration risks. Our findings on structural controls and depth targeting support low-impact mining and efficient resource development in the region.